Clinical Guidelines for Diagnosis and Treatment of Knee Osteoarthritis(Xibibing)in Orthopedics and Traumatology of Traditional Chinese Medicine - Working Group on Setting up Guidelines for Diagnosis and Treatment of Knee Osteoarthritis (Xibibing) in Orthopedics Section of China Association of Chinese Medicine (康复学报)
Knee osteoarthritis(KOA, Xibibing)is a common disease in people over 40, and the disability rate is 53%.Based on evidence-based medicine, the clinical practice guidelines of traditional Chinese medicine(TCM)for Xibibing(KOA), it is necessary to standardize TCM clinical diagnosis and treatment technology. The characteristics and advantages of syndrome differentiation and treatment are reflected in the development of TCM clinical diagnosis and treatment guidelines for Xibibing(KOA).This guidance is mainly based on the principle of evidence-based medicine and TCM literature and the expert consensus, the expert argumentation, peer opinions, clinical evaluation, etc. The guidance includes terms and definitions, diagnosis, classification of the disease stages and syndrome differentiation, treatment of the disease(KOA), for the treatment of traumatology, combine traditional Chinese and western medicine orthopedics, Chinese medicine, acupuncture, massage, rehabilitation and rheumatism clinicians. The treatment section for Xibibing(KOA)is divided into three, non-drug treatment, drug treatment and surgical treatment, and describes the indications and recommended levels of various treatment methods. Non-drug treatment mainly includes health education, skill training, manipulation, acupuncture and moxibustion, acupotomology, physiotherapy and other therapies. In the drug treatment part, it is discussed from the aspects of external medicine, injection medicine, syndrome differentiation and internal treatment of traditional Chinese medicine, Chinese patent medicine, oral medicine for symptom control, diseases modifying osteoarthritis drugs(DMOAD)and cartilage protectant. Surgical treatment includes arthroscopic surgery, osteotomy, artificial joint replacement and arthrodesis. The guideline is of importance for clinical applicability, safety and effectiveness.